Gold or Silver: An Alternative to Investing - Iván Vacio (Apuntes del CENES)
Throughout history, gold has been a highly valued investment, especially in times of crisis. In recent years, however, silver has attracted the attention of investors for its performance in terms of returns and price. Therefore, the objective of this research was to determine which of the two metals is the best to invest in. In this sense, an empirical method was developed based on the most common tests found in the literature, which included a financial integration with macroeconomic variables of the United States; predictability and trend analysis; return loss rate; volatility analysis; and annual returns. A quantitative research approach limited to the United States of America was established. The variables mainly used were the prices of gold and silver and their returns between 1990 and 2024. The statistical methods used in these tests were: Multiple Linear Correlation; Cubic ARIMA, GARCH and Polynomial Regression; Defects per Million Opportunities (DPMO); Bonett test for Difference of Variances; and Short, Medium and Long Term Returns Analysis. In order to synthesize and compare the results of the tests, an evaluation method based on the Pugh Matrix was used. As a result, gold received a score of +1, while silver got a value of -1, reaching the conclusion that of the two metals, gold is the best to invest in. Some findings and considerations are mentioned at the end.